Conventional and fast field cycling relaxometry study of the molecular dynamics in polymer nanocomposites for use as drug delivery systems - Sebastião, Pedro J. (2016)
This article presents a molecular dynamics study performed by combining conventional and fast-field cycling NMR relaxation techniques in nanocomposite systems for the optimization of drug delivery systems. The biodegradable polymers polycaprolactone, polylactide, polyvinyl alcohol and maize starch were used as base polymers and they were modified by incorporation of nanoparticles and/or cross-linking reactions, in order to understand the interaction between the bioactive molecules and the supporting matrix for a controlled drug release. Nevirapine was used as a testing bioactive drug. H spin-lattice relaxation times were measured for Larmor frequencies between 10 kHz and 300 MHz to obtain information about molecular motions in different time scales for comprehensive analysis of the possible interactions of the polymer matrices, modified nanoparticles and bioactive molecules. All systems presented some degree of crystallinity and poly-exponential decay of magnetization in the spin-lattice relaxation. The shortest spin-lattice relaxation times were assigned to the more amorphous regions and the relaxation dispersion was similar to that found in polymer melts. The effects of both nanoparticles and bioactive molecules on the molecular dynamics of the polymer matrices were clearly detected. The results show that NMR relaxometry study covers a broad range of frequencies and it is a powerful and suitable method to characterize nanocomposite systems at the molecular scale, provides information about the mobility of polymer chains and the strength of the interaction between polymers/nanoparticles. This information helps to make inferences about drug confinement level inside the systems, which can have a direct influence on the drug release. It is extremely important to know the exact drug release mechanism of bioactive molecules in a medical treatment. The main results indicated that the NMR techniques used were able to evaluate the molecular dynamics of the nanocomposites studied. It can be pointed out that PCL/clay nanocomposites containing nevirapine drug, caused a compensating effect regarding to the distribution of correlation times for the molecular segment motions and the drugs interferes in the nanomaterial molecular dynamics.